Tipificación de Candida en muestras de secreción vaginal de mujeres en edad fértil que acuden al Centro de Salud N° 1 de la ciudad de Loja - Cotacachi Tuquerres, Diana Maritza (2018)
Candida is a type of yeast-like fungus found in different areas of the body, such as the vagina; however, it is considered an opportunistic pathogen that depends on virulence factors favoring the host to cause infection. The most frequently isolated species in the vaginal area is Candida albicans, but nevertheless, studies carried out nowadays indicate that in recent years it has increased the species of Candida not albicans such as Candida glabrata, Candida tropicalis, Candida pseudotropicalis and Candida krusei. In order to carry out the present investigation, the following objectives were proposed: to identify the presence of fungal structures in samples of vaginal secretion by means of the KOH test, to identify the growth of colonies in Sabouraud Agar and to identify the species of Candida through the culture in CHROMagar- Candida. In the present descriptive and cross-sectional study, a total of 130 vaginal discharge samples were obtained; the tests that were applied were: KOH (Potassium hydroxide), Sabouraud Agar, CHROMagar-Candida. After the application of the KOH test the following result was obtained: yeasts (60.8%), pseudohyphae (13.1%) and mixed structures of yeasts and pseudohyphae (26.1%). Likewise, after carrying out the cultivation in Sabouraud Agar, it was observed that of the 100% of the samples processed, all presented the growth of smooth, creamy and yellowish-white colonies, characteristics of Candida; finally the culture in CHROMagar-Candida allowed to identify the following species of Candida: with greater predominance Candida krusei with 69.2%, followed by Candida albicans with 29.2%, and Candida glabrata with 1.6%. Key words: Virulence factors, Candida, KOH, Sabouraud Agar, CHROMagar-Candida.